DYSLIPIDEMIA: A PRACTICAL APPROACH (Fiep Bulletin - online, 2013)
The Dyslipidemia are related like an abnormality in blood levels of lipids and lipoproteins metabolism, with the risk of developing coronary disease. These are related to genetics tendency, food rich in fats and sedentary lifestyle, which together lead to weight gain or overweight and that in its consequence, end up harming the quality of life. However, the dyslipidemia, which affects adults generally have been increasingly diagnosed early in children and adolescents due to the sedentary lifestyle associated with family history of CHD (coronary artery disease). The methodology used in the preparation of this text was to review. The conclusion showed that the intake of balanced diet and regular exercise and, in severe cases, the use of medicines can balance this situation of dyslipidemia in children and adolescents. The reduction in LDL-cholesterol and increase in HDL-cholesterol levels monitored and guided by health professionals provide reduction in cardiovascular risk and adulthood with a better quality of life.
Keywords: Dyslipidemia; quality of life; fitness